The antioxidant activity of diosgenin, a plant steroid sapogenin, in C2C12 myoblasts is achieved by blocking mitochondrial ROS production - Cheol Park; Gi-Young Kim; Yung Hyun Choi (Applied Biological Chemistry)
Abstract Diosgenin, a plant-derived steroid sapogenin, has been reported to have many health benefits, including antioxidant activity. Although oxidative stress is a major factor impeding the differentiation and homeostasis of skeletal muscles, its antioxidant activity in skeletal muscle cells has not been thoroughly studied. This study aimed to explore the protective mechanisms of diosgenin against oxidative damage in skeletal muscle cells. C2C12 murine myoblasts were pretreated with nontoxic concentrations of diosgenin and exposed to hydrogen peroxide (H2O2) to mimic oxidative stress. The results of this study showed that diosgenin significantly reduced H2O2-induced cytotoxicity, blocked the formation of comet tails, and increased the levels of 8-hydroxy-2’-deoxyguanosine, which are representative biomarkers of DNA damage. In addition, diosgenin counteracted H2O2-induced apoptosis by enhancing the Bax/Bcl-2 expression ratio and suppressing the activation of the caspase cascade, which is associated with the blockade of cytochrome c release into the cytoplasm by maintaining mitochondrial stability. Furthermore, diosgenin eliminated the production of intracellular and mitochondrial reactive oxygen species (ROS) by restoring glutathione (GSH) content and the activities of antioxidant enzymes such as GSH peroxidase 1 and manganese-dependent superoxide dismutase, which were inhibited by H2O2. Therefore, diosgenin protects C2C12 myoblasts from oxidative damage by attenuating mitochondrial ROS generation and regulating the mitochondrial apoptotic pathway.